Rebound-associated vertebral fractures after discontinuation of denosumab—from clinic and biomechanics. Issue 5 (May 2016) - Popp, A.; Zysset, P.; Lippuner, K.
Abstract Summary Rebound-associated vertebral fractures may follow treatment discontinuation of highly potent reversible bone antiresorptives, resulting from the synergy of rapid bone resorption and accelerated microdamage accumulation in trabecular bone. Introduction The purposes of this study are to characterize rebound-associated vertebral fractures following the discontinuation of a highly potent reversible antiresorptive therapy based on clinical observation and propose a pathophysiological rationale. Methods This study is a case report of multiple vertebral fractures early after discontinuation of denosumab therapy in a patient with hormone receptor-positive non-metastatic breast cancer treated with an aromatase inhibitor. Results Discontinuation of highly potent reversible bone antiresorptives such as denosumab may expose patients to an increased fracture risk due to the joined effects of absent microdamage repair during therapy followed by synchronous excess activation of multiple bone remodelling units at the time of loss-of-effect. We suggest the term rebound-associated vertebral fractures (RVF) for this phenomenon characterized by the presence of multiple new clinical vertebral fractures, associated with either no or low trauma, in a context consistent with the presence of high bone turnover and rapid loss of lumbar spine bone mineral density (BMD) occurring within 3 to 12 months after discontinuation (loss-of-effect) of a reversible antiresorptive therapy in the absence of secondary causes of bone loss or fractures. Unlike atypical femoral fractures that emerge from failure of microdamage repair in cortical bone with long-term antiresorptive treatment, RVF originate from the synergy of rapid bone resorption and accelerated microdamage accumulation in trabecular bone triggered by the discontinuation of highly potent reversible antiresorptives. Conclusions Studies are urgently needed to i) prove the underlying pathophysiological processes suggested above, ii) establish the predictive criteria exposing patients to an increased risk of RVF, and iii) determine appropriate treatment regimens to be applied in such patients.